Peri-conceptional diet patterns and the risk of gestational diabetes mellitus in South Indian women - Anvesha Mahendra; Sarah H Kehoe; Sarah R Crozier; Kalyanaraman Kumaran; GV Krishnaveni; Nalini Arun; Padmaja; Prakash Kini; Unaiza Taskeen; Krupa T Kombanda; Matthew Johnson; Clive Osmond; et al. (Cambridge University Press, 2023)
Abstract Objective: To identify peri-conceptional diet patterns among women in Bangalore and examine their associations with risk of gestational diabetes mellitus (GDM). Design: BAngalore Nutrition Gestational diabetes LifEstyle Study, started in June 2016, was a prospective observational study, in which women were recruited at 5-16 weeks' gestation. Peri-conceptional diet was recalled at recruitment, using a validated 224-item FFQ. GDM was assessed by a 75-g oral glucose tolerance test at 24-28 weeks' gestation, applying WHO 2013 criteria. Diet patterns were identified using principal component analysis, and diet pattern-GDM associations were examined using multivariate logistic regression, adjusting for 'a priori' confounders. Setting: Antenatal clinics of two hospitals, Bangalore, South India. Participants: Seven hundred and eighty-five pregnant women of varied socio-economic status. Results: GDM prevalence was 22 %. Three diet patterns were identified: (a) high-diversity, urban (HDU) characterised by diverse, home-cooked and processed foods was associated with older, more affluent, better-educated and urban women; (b) rice-fried snacks-chicken-sweets (RFCS), characterised by low diet diversity, was associated with younger, less-educated, and lower-income, rural and joint families; and (c) healthy, traditional vegetarian (HTV), characterised by home-cooked vegetarian and non-processed foods, was associated with less-educated, more affluent, and rural and joint families. The HDU pattern was associated with a lower GDM risk (adjusted odds ratio (aOR): 0·80/sd, 95 % CI (0·64, 0·99), P = 0·04) after adjusting for confounders. BMI was strongly related to GDM risk and possibly mediated diet-GDM associations. Conclusions: The findings support global recommendations to encourage women to attain a healthy pre-pregnancy BMI and increase diet diversity. Both healthy and unhealthy foods in the patterns indicate low awareness about healthy foods and a need for public education.